Improving stability in developing nations through automation 2006 : a proceedings volume from the IFAC Conference on Supplemental Ways for Improving International Stability through Automation ISA '06, 15-17 June 2006, Prishtina, Kosovo - Kopacek, Peter (Elsevier, 2006)
The contributions included in this volume cover a very broad field of interest for subjects such as social aspects of technology transfer, managing the introduction of technological change, ethical aspects, technology and environmental stability, and anticipating secondary and tertiary effects of technological development.